Sufistic Da'wah and Its Challenges in Facing Globalization Currents at Parsulukan Aek Salak and Babussalam Rodang Selamat in Padang Lawas - Rosma yani (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2026)
This study examines the implementation and spiritual development based on Sufistic da'wah and its challenges in facing the currents of globalization at Parsulukan Aek Salak and Babussalam Rodang Selamat in Padang Lawas. Globalization has brought social changes that weaken religious awareness and increase materialistic orientation within society. This condition requires a da'wah approach that is capable of addressing the inner spiritual dimension more deeply. The study employs a qualitative approach with a descriptive method using observation, interviews, and documentation techniques. The findings reveal that the implementation of Sufistic da'wah is carried out through structured spiritual activities such as dhikr, suluk, tawajuh, and continuous spiritual guidance under the supervision of a mursyid. This spiritual development process enhances religious awareness, strengthens moral character, and builds community spiritual resilience. Sufistic da'wah also contributes to maintaining a balance between worldly life and the hereafter while fostering a moderate and inclusive religious character. The challenges faced include the influence of globalization that promotes materialistic thinking, the advancement of information technology, and shifts in religious behavior patterns. This study confirms that Sufistic da'wah remains highly relevant as a strategy for spiritual development in addressing the dynamics of globalization and serves as a solution to moral and spiritual crises in modern society.